El historiador gerundense Carles Rahola: desde los márgenes, la centralidad - Mallart, Lucila (Historiografías, 2021)
This article presents a historiographical approach to the work of Carles Rahola (1881-1939), a historian from Girona who is especially known for his contributions on the Napoleonic domination in Catalonia. Although his work has been partially studied and republished in recent decades, it has not been analysed in an explicit methodological way. This study examines Rahola’s engagement with local history, the effects of his non-professional context, his relationships with Catalan, Spanish and European intellectuals, and the meaning of the use of a narrative style in his work. Keywords Local history, amateur history, narrative history, Napoleonic studies, Catalan history